TEKS KRÉMATORIUM, ANGGOTA DEWAN, SUNDEL TANAH, NYINGNYING, DAN LULUS DALAM PUPULAN SATUA BALI MODERN SUNDEL TANAH ANALISIS AMANAT - Widi Adnyana, I Komang; Suryati, I Made; Agung Mulyawati, Tjokorda Istri (Humanis; Volume 16. No. 2. Agustus 2016, 2017)
This research entitled “Teks Krematorium, Anggota Dewan, Sundel Tanah, Nyingnying, dan Lulus Analisis Amanat”. It used structural theory based on the structure and instruction. This research has function to describe the structure that set up Teks Krematorium, Anggota Dewan, Sundel Tanah, Nyingnying, dan Lulus, and to analyze the instruction appeared on the Satua Bali Modern Krematorium, Anggota Dewan, Sundel Tanah, Nyingnying dan Lulus. The method used in the process of providing data was gathering method by using record-keeping and translating techniques. On the process of analyzing data, this research used qualitative method. It was supported by analytical-descriptive technique. On the process of analyzing data, the writer used informal method with deductive-inductive techniques. The result shows that: (1) there are six components of structural analysis that set up Teks Krematorium, Anggota Dewan, Sundel Tanah, Nyingnying, dan Lulus, such as incident, plot, characters, characterization, setting, theme, and the instruction was analyzed on the different sub-chapter. The plot of Teks Krematorium, Anggota Dewan, Sundel Tanah, Nyingnying, dan Lulus are return-back and progressive plot. Besides, the characters and characterization can be seen through the existence of prominent figure from the physiological, sociological, psychological sides with the socio-critical theme on the setting of place, time and situation. (2) The instruction appeared Satua Bali Modern Krematorium, Anggota Dewan, Sundel Tanah, Nyingnying dan Lulus are on: the instruction of solution, introspection, karmaphala and good leadership.
Keywords: short story, structure, instruction